The suitability of pelleted diets in the cage culture of the giant gourami, Osphronemus goramy (Lacepede) - Ang, Kok Jee; Cheah, Sin Hock; Tan, G. H.; Law, A. T. (1987)
In the first trial, fish (8.4g in weight) were subjected to 4 treatments with 3 replicates/treatment at a stocking, rate of 15 fish/m for 12 weeks and fed a daily ration of 10% body weight. The 4 treatments were as follows: I-Colocasia leaves; II-10% crude protein (C.P.) diet, III-20% C.P. diet and IV-40% C.P. diet. At the end of the study period, the incremental weights in Treatment I, II, III and IV were 5.7 g, 18.1 g, 33.1 g, and 44.7 g respectively. The FCR for treatment II, III and IV were 7.33, 5.22 and 4.94 respectively while the PER for treatment II, III and IV were 1.35, 0.99 and 0.49 respectively. The Specific Growth Rate for Treatment I, II, III and IV were 0.61%/day, l.4%/day, 1.9%/day and 2.2%/day respectively. The survival rate in all the treatments was high. In the second trial, fish (13.8 g - 14.9 g) were subjzcted to 3 treatments with 3 replicates/treatment at a stocking rate of 15 fish/3m for a period of 18 weeks and fed with diet 1-25% C.P., diet 2-35.% C.P. and diet 3-45% C.P. at a daily ration of 10% body weight. At the termination of the study the incremental weights in Treatment I, 2 and 3 were 100.6 g, 166.6 g and 182.3 g respectively. The FCR in treatment 1, 2 and 3 were 5.53, 4.40 and 4.58 respectively while the PER values were 0.724, 0.650 and 0.49 in treatment 1, 2, and 3 respectively. The 'K' factor in diet 3 (35.% C.P.) recorded the highest value of 5.20 and the best FCR of 4.40 indicating the superiority of this diet over the other diets tested. The mean values for water quality parameters in the stUdy area cannot be considered ideal for aquaculture as it has a low pH (5.5), low alkalinity (7.0 mg) and low conductivity (24.7µMHOS).